PERCEPTIONS (LECTURE, TEACHER, AND STUDENTS) ON SCIENCE TEACHING PROCESS FOR PPL PHYSICS STUDENT - Nugroho Prasetya Adi; Lutfatul Latifah; Firdaus Firdaus; Intan Masruroh Swastika (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
The Praktik Pengalaman Lapangan (PPL) program is an effort to introduce prospective teacher students to the world of their profession. Praktik Pengalaman lapangan is one of the best programs of the Faculty of Teaching Education (FITK), Sains Al-Qur’an University in providing opportunities for its students to practice teaching directly in the field. The research is used a field research in qualitative. Qualititative is a type of research that is observing an object then data was analyzed using descriptive. This research was used questionnaire of student response to collect the data. The data of this research were analyzed using descriptive and student response. Based on the data analysis carried out, it was concluded that students had very good science teaching abilities based on the assessments of lecturers and teachers, as well as good based on student assessments of the learning process carried out by UNSIQ PPL students majoring in physics education.